Risk Factors and metabolic indicators associated with the percentage frequency of subclinical Ketosis on Ouled Djellal Ewes in Eastern Highlands of Algeria - Meriem Bouzenzana; Abdennour Azizi; Sabah Hanachi; Karima Benembarek; Mohammed–Ezine Zebiri; Nedjoua Arzour–Lakehal; Toufik Meziane (Revista Científica, 2024)
This study investigated the frequency, risk factors, and metabolic indicators for detecting subclinical ketosis (SCK) in Ouled Djellal ewes. Out of 54 enrolled ewes, those with BHB ≥ 0.86 mmol·L-1 without clinical signs formed the SCK group, while ewes with BHB < 0.86 mmol·L-1 were healthy controls, either in late pregnancy or early lactation. The SCK frequency was higher in early lactation (37%). Increased risk was associated with twin–bearing (OR=4.96, 95%CI=1.967–12.503, P=0.001) and thin ewes with BCS < 2.5 (OR=2.74, 95%CI=0.71–10.73, P=0.003). SCK ewes had significantly lower glucose, triglycerides, cholesterol, Ca, Mg, Na, and K levels, but higher AST, ALT, GGT, ALP, LDH, and CK levels. The best diagnostic indicators were Ca (AUC 94.4%, cut–off < 81 g·L-1, SE 77.46%, SP 100%), AST (AUC 84.4%, cut–off > 94.19 U·L-1, SE 74.65%, SP 83.78%), and K (AUC 79.3%, cut–off 4.1 mmol·L-1, SE 71.83%, SP 75.68%). Monitoring BHB and BCS, especially in twin–bearing ewes during the transition period, is recommended for ketosis prevention. Further large–scale validation of these metabolic indicators as SCK predictors in Ouled Djellal ewes is warranted.